Perception and Impact on Oral Health in the Daily Activities of a Homeless Population: a cross-sectional study - Saraiva, Amanda Meira (2020)
Introduction: The understanding of the homeless population (HP) about their oral health can contribute to the planning of dental care actions.Objective: To evaluate sociodemographic profile, perception and impact of oral health on daily activities (OHDA) of an HP.Method: This is a cross-sectional, descriptive, retrospective study conducted with HP in a municipality in northwestern Paraná-Brazil. Interviews were conducted on 117 individuals using a quantitative and qualitative questionnaire with demographic and oral health variables. Bivariate analyzes were performed with Chi-square test at a significance level of 5%.Results: Most were male (92.3%), with an average of 35.8 years, without a partner (75.2%), with up to 8 years of schooling (66.7%), non-white skin (61.5%) and average daily income of up to 30 reais (38.5%). Most reported not having a profession (81.2%) and being on the street for more than 2 years (54.7%). Most reported mouth problems in the last 6 months (45.3%) and 72.6% of HP had negative OHDA, resulting in a statistically significant association (p = 0.0089).Conclusion: The results outlined the profile and perception of oral problems that negatively impacted their daily activities, highlighting the importance of considering subjective aspects in the dental care of the HP to plan oral health promotion and protection actions.